Venous Disorders Current Concepts (Springer Singapore, 2018)
Venous disorders are extremely common in clinical practice, and recent years have seen a number of changes in the treatment of these conditions. This book covers the advances in our understanding and the management of venous disorders - both superficial and deep. It includes up-to-date reviews on the hemodynamics of venous circulation in the lower limbs, deep venous reflux, novel biomarkers in deep vein thrombosis, post thrombotic syndrome, infra-popliteal DVT, relevance of wave length in laser treatment of varicose veins, pelvic congestion syndrome, May-Thurner syndrome, nut cracker syndrome, endothermal heat-induced thrombosis, recurrent varicose veins, and venous trauma. It also discusses important topics such as one-stop vein clinics, alternatives for venous ulcer treatment, venous anatomy, therapeutic options in lymphedema, nerve damage during endovenous thermal ablation, newer oral anticoagulants, compression therapy for venous ulcer, sclerotherapy for varicose veins and thrombolysis for DVT. Written by leading experts in their field, this book is a key resource for practicing vein physicians and surgeons, and postgraduates in surgery training programs, enabling them to incorporate the latest advances into their day-to-day practice.